The very strong coastal El Niño in 1925 in the far-eastern Pacific - Takahashi, Ken (2018)
The 1925 El Niño (EN) event was the third strongest in the twentieth century according to its impacts in the far-eastern Pacific (FEP) associated with severe rainfall and flooding in coastal northern Peru and Ecuador in February–April 1925. In this study we gathered and synthesised a large diversity of in situ observations to provide a new assessment of this event from a modern perspective. In contrast to the extreme 1982–1983 and 1997–1998 events, this very strong “coastal El Niño” in early 1925 was characterised by warm conditions in the FEP, but cool conditions elsewhere in the central Pacific. Hydrographic and tide-gauge data indicate that downwelling equatorial Kelvin waves had little role in its initiation. Instead, ship data indicate an abrupt onset of strong northerly winds across the equator and the strengthening/weakening of the intertropical convergence zones (ITCZ) south/north of the equator. Observations indicate lack of external atmospheric forcing by the Panama gap jet and the south Pacific anticyclone and suggest that the coupled ocean–atmosphere feedback dynamics associated with the ITCZs, northerly winds, and the north–south SST asymmetry in the FEP lead to the enhancement of the seasonal cycle that produced this EN event. We propose that the cold conditions in the western-central equatorial Pacific, through its teleconnection effects on the FEP, helped destabilize the ITCZ and enhanced the meridional ocean–atmosphere feedback, as well as helping produce the very strong coastal rainfall. This is indicated by the nonlinear relation between the Piura river record at 5°S and the SST difference between the FEP and the western-central equatorial Pacific, a stability proxy. In summary, there are two types of EN events with very strong impacts in the FEP, both apparently associated with nonlinear convective feedbacks but with very different dynamics: the very strong warm ENSO events like 1982–1983 and 1997–1998, and the very strong “coastal” EN events like 1925.